MEMBENTUK KARAKTER PEDULI LINGKUNGAN PADA PEMUDA REMAJA DI DESA PETUK LITI - Juandi Juandi; Yamowa'a Bate'e, Yeremia, Betris, Meysa Mardalena Sari, Lusia Nefri, Sri Ekadamanyanty, Linta, Depi (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to cultivate environmentally conscious character among youth in Petuk Liti Village, Central Kalimantan. The main issue addressed is the low awareness and participation of teenagers in preserving the environment amidst increasing ecological pressure from human activities. A qualitative approach was used, combining case studies and literature review. Data collection involved in-depth interviews with village officials, religious leaders, educators, residents, and students, as well as direct observation around schools and places of worship. The findings show that fostering environmental awareness in youth can be effectively achieved through the synergy of formal education, non-formal learning, family involvement, and the influence of community and religious leaders. Local wisdom and spiritual values play a crucial role in shaping emotional ties between youth and their environment. Role models and active participation in environmental initiatives significantly strengthen character development. The study concludes that a holistic approach engaging multiple stakeholders fosters a generation that is not only intellectually competent but also ecologically conscious. These findings contribute to the development of contextual, value-based character education rooted in local wisdom and culture